Prediksi Volatilitas Harga Jual Produk Pada E-Commerce Untuk Independent Stockashtic Data - Abdi Julianto, Dwana; Febby Olivia, Ladyka; Hendrik, Billy (Riset Sinergi Indonesia (RISINDO), 2023)
The development of technology and information has changed people's behavior from an industrial society to an innovative society. This change can be seen from the growth of people's consumption habits from trading through physical stores (offline) to trading through electronic systems, or what is often referred to as. Online shopping. The logistics service is a distribution operator in the downstream region, whose job it is to deliver products from the delivery center of the online store to the end customer. Logistics services must fulfill consumer demands in accordance with the Service Level Agreement (SLA). Uncertain demand is the biggest challenge for logistics service providers. As in the case study used in this study, PT ABC experienced an overload when fulfilling requests from PT XYZ, an e-commerce company. The overload was caused by PT ABC's reluctance to face a very significant increase in demand due to changes in the selling price of product A at PT XYZ's online store. This study proposes a model to predict the selling price of product A at PT XYZ's online store using a Monte Carlo simulation model with independent variables. The simulation was run with 1000 trials and produced the lowest MAPE out of 322 trials, namely 0.122%.